Radiofrequency catheter ablation for idiopathic right ventricular tachycardia with special reference to morphological variation and long-term outcome. Issue 3 (September 1997) - Chinushi, M.; Aizawa, Y.; Takahashi, K.; Kitazawa, H.; Shibata, A.
Abstract : OBJECTIVE: To assess the long term outcome of radiofrequency (RF) catheter ablation for idiopathic ventricular tachycardia (VT) originating from the outflow tract of the right ventricle, with special reference to the morphological variation in the VT-QRS complexes. PATIENTS: 13 patients whose ventricular tachycardia was treated with RF ablation were followed up more than 18 months after RF ablation. RESULTS: Endocardial mapping revealed the various extensions of ventricular tachycardia origin (from 0.5 x 0.5 cm to 2.0 x 2.0 cm) in which the earliest local electrogram was recorded during ventricular tachycardia. In all five tachycardias from a relatively wider origin (more than 0.5 x 0.5 cm) and in four of eight from a narrow origin (< 0.5 x 0.5 cm), subtle morphological variation in the VT-QRS complexes was observed. In tachycardias with morphological variation, the local electrogram at the tachycardia origin also showed concomitant variation in morphology and activation sequence. Ventricular tachycardia from a narrow site was eliminated by RF ablation to the confined site, but a larger number of RF applications was required in tachycardias from a wider origin. All 13 tachycardias were successfully ablated by RF current, and during the follow up period of 28.2 (SD 7.2) months, recurrence was observed in only one patient who had a wider origin. CONCLUSIONS: Long term efficacy of RF ablation was excellent in idiopathic ventricular tachycardia originating from the outflow tract of the right ventricle. Subtle morphological variations were frequently observed in this type of ventricular tachycardia, and about half of them represented a relatively wider arrhythmogenic area.